3D Scanner from Two Web Cameras - Gevorgyan , Aram V.; Sarukhanyan, Hakob G. (Mathematical Problems of Computer Science, 2021)
In this paper we present an approach how to build 3D scanner using two ordinary web cameras. This approach is based on stereovision and is beneficial from the other 3D scanners that it doesn’t need laser, structured light or other expensive sensors. We put the object in front of the cameras at a distance about 40-50 cm and rotate it at small degrees. For every rotation we compute the disparity map from two cameras and then get the depth map in the form of point cloud. Then we filter out our object from the scene and then merge object point clouds from different views to get a full 3D model.